Single and Multiple Stimuli-Responsive Polymer Particles for Controlled Drug Delivery - Aida López Ruiz; Ann Ramirez; Kathleen McEnnis (MDPI AG, 2022)
Polymers that can change their properties in response to an external or internal stimulus have become an interesting platform for drug delivery systems. Polymeric nanoparticles can be used to decrease the toxicity of drugs, improve the circulation of hydrophobic drugs, and increase a drug's efficacy. Furthermore, polymers that are sensitive to specific stimuli can be used to achieve controlled release of drugs into specific areas of the body. This review discusses the different stimuli that can be used for controlled drug delivery based on internal and external stimuli. Internal stimuli have been defined as events that evoke changes in different characteristics, inside the body, such as changes in pH, redox potential, and temperature. External stimuli have been defined as the use of an external source such as light and ultrasound to implement such changes. Special attention has been paid to the particular chemical structures that need to be incorporated into polymers to achieve the desired stimuli response. A current trend in this field is the incorporation of several stimuli in a single polymer to achieve higher specificity. Therefore, to access the most recent advances in stimuli-responsive polymers, the focus of this review is to combine several stimuli. The combination of different stimuli is discussed along with the chemical structures that can produce it.